Impaired DNase1‐mediated degradation of neutrophil extracellular traps is associated with acute thrombotic microangiopathies. (13th April 2015) - Jiménez‐Alcázar, M.; Napirei, M.; Panda, R.; Köhler, E. C.; Kremer Hovinga, J. A.; Mannherz, H. G.; Peine, S.; Renné, T.; Lämmle, B.; Fuchs, T. A.
Summary Background Acute thrombotic microangiopathies (TMAs) are characterized by excessive microvascular thrombosis and are associated with markers of neutrophil extracellular traps (NETs) in plasma. NETs are composed of DNA fibers and promote thrombus formation through the activation of platelets and clotting factors. Objective The efficient removal of NETs may be required to prevent excessive thrombosis such as in TMAs. To test this hypothesis, we investigated whether TMAs are associated with a defect in the degradation of NETs. Methods and Results We show that NETs generated in vitro were efficiently degraded by plasma from healthy donors. However, NETs remained stable after exposure to plasma from TMA patients. The inability to degrade NETs was linked to a reduced DNase activity in TMA plasma. Plasma DNase1 was required for efficient NET degradation and TMA plasma showed decreased levels of this enzyme. Supplementation of TMA plasma with recombinant human DNase1 restored NET‐degradation activity. Conclusions Our data indicate that DNase1‐mediated degradation of NETs is impaired in patients with TMAs. The role of plasma DNases in thrombosis is, as of yet, poorly understood. Reduced plasma DNase1 activity may cause the persistence of pro‐thrombotic NETs and thus promote microvascular thrombosis in TMA patients.